2018
DOI: 10.1002/ptr.6079
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin improves postpartum hypogalactia in milk‐deficient mice via stimulating prolactin production in pituitary gland

Abstract: Postpartum dysgalactia is a common clinical problem for lactating women. Seeking out the safe and efficient phytoestrogens will be a promising strategy for postpartum dysgalactia therapy. In this study, the postpartum mice within four groups, including control group, the model group, and the treatment groups intragastrically administrated with normal saline, bromocriptine, bromocriptine plus 17α-ethinyl estradiol, and bromocriptine plus quercetin, respectively, were used. The results showed that quercetin, a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Lignans (lariciresinol, pinoresinol) and phenolic acids also contribute ( Herchi et al 2014 ; Zhong et al 2021 ). Quercetin induces sensitivity to prolactin and the expression of stearoyl-CoA desaturase and fatty acid synthase in the murine mammary gland ( Lin et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignans (lariciresinol, pinoresinol) and phenolic acids also contribute ( Herchi et al 2014 ; Zhong et al 2021 ). Quercetin induces sensitivity to prolactin and the expression of stearoyl-CoA desaturase and fatty acid synthase in the murine mammary gland ( Lin et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Certain antioxidant effects on human milk lipids were reported ( Poniedziałek et al 2018 ; Valls-Bellés et al 2021 ). Although the physiological mechanisms remain unclear, they may protect against peroxidative damage-related lipid degradation, upregulate gene expression related to lipid metabolism in the mammary gland, modulate neuroendocrine pathways, and enhance milk lipid clearance ( Codini et al 2020 ; Downing et al 2017 ; Lin et al 2018 ). Thus, additional biochemical studies are still needed because lipids are indispensable nutrients for healthy child development ( Brink and Lönnerdal 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Papaya leaves contain alkaloid compounds such as carpaine and pseudocarpaine, enzymes (papain, chymopapain, and cystatin), tocopherol, ascorbic acid, tannins, nicotinic acid, saponins, peonidins, chlorogenic acid, the coumarin compound, and phenolic compounds as the main phytochemicals and flavonoids [34], [35], [36]. Quercetin as a phytoestrogen can stimulate prolactin production [37]. The content of metabolite compounds in papaya leaves is the same as that in three types of plants that are widely used as a galactogogue, namely Trigonella foenum-graecum (fenugreek), Asparagus racemosus (shatavari), and Moringa oleifera (malunggay) [38].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the 'drugs-targets-disease' network, the results of screening the bioactive compounds of daylily showed that a total number of 62 compounds positively affect breast milk secretion, with quercetin, kaempferol, thymidine, chlorogenic acid, caffeic acid, and rutin being the most important compounds. The published literature has indicated that quercetin initiated the lactation process by promoting the prolactin receptor (PRLR) expression and increased the expression of β-casein, stearoyl-coenzyme a desaturase, fatty acid synthase, and α-lactalbumin in mammary tissue, which are responsible for the production of fatty acids, lactose, and galactose in milk [31]. Rutin promotes the regulation of hormone secretion associated with the development of breast tissue, such as estrogen, growth hormone, and PRL [32].…”
Section: Discussionmentioning
confidence: 99%
“…Network pharmacology prediction results showed that, among the common targets between daylily and lactation, there were several targets involved in regulation of breast involution [41], including STAT3, MAPK1, and IL 6, and some targets with the function of the functional differentiation of mammary gland [42,43], such as CCND1, PRLR, and TGFB1, as well as targets which have ability of regulating the biosynthesis of milk components [39], including AKT1, TF, and INS, etc. Furthermore, quercetin has been reported to promote milk secretion by significantly increasing PRLR levels [31]. Kaempferol has a significant potential to inhibit STAT3 and IL6 expression [44].…”
Section: Discussionmentioning
confidence: 99%